Cytogenatic Analysis In Kacholam - Rekha K (Department of Agricultural Botany, College of Horticulture, 1993)
The present study on cytogenetics of Kaempferia galanga L. in relation to seed set was undertaken at the Department of Agricultural Botany, College of Horticulture, Vellanikkara during the period 1991-93. A local selection ‘Vellanikkara’ grown under garden of AICRP on Medicinal and Aromatic Plants was used for the study. The major objectives were to confirm the existing reports on chromosome numbers, to determine the nature of pliody based on meiotic studies and to find out reasons for seedlessness in the crop in cytology and floral biology. The procedure for karyotype studies in Kaempferia was standardized. Pre-treatment of the roots in – bromonaphthalene for hours at 40C followed by fixation in Carnoy’s fluid for 24 hours and staining overnight in Snow’s carmine were effective in getting best cytological preparations. Mitotic studies revealed that this species is a polyploid and with all probability a pentaploid with 2n = 5x = 55. This somatic chromosome number is being reported for the first time in Kaempferia galanga L. The karyotype was found to be a symmetric one and belonged to ‘1a’ group of Stebbins (1958) classification. Meiotic studies revealed the presence of associations involving three, four, five and six chromosomes in addition to the bivalents and univalent. However, the number of multivalents were much less than expected and later meiotic abnormalities were rather almost absent. Pollen grains also exhibited reasonable fertility and viability. Based on both mitotic and meiotic studies it was indicated that Kaempferia galanga L. is a segmental allopolyploid with five sets of genomes designated as A1A2A2A2A2. Studies on floral morphology and artificial pollinations to induce seed set led to the conclusion that seedlessness in the crop is mainly due to the incompatibility factors in the style and stigma. The spiny stigma does not permit the proper adherence and germination of the pollen grains and the pollen tube growth attained was not sufficient to surpass the lengthy style and to reach the ovary. Attempts to induce seed set by hand pollination and stub pollination also failed.